2023
DOI: 10.1002/jcp.31068
|View full text |Cite
|
Sign up to set email alerts
|

METTL16 promotes osteosarcoma progression by downregulating VPS33B in an m6A‐dependent manner

Abstract: N6‐methyladenosine (m6A) is one of the main epitranscriptomic modifications that accelerates the progression of malignant tumors by modifying RNA. Methyltransferase‐like 16 (METTL16) is a newly identified methyltransferase that has been found to play an important oncogenic role in a few malignancies; however, its function in osteosarcoma (OS) remains unclear. In this study, METTL16 was found to be upregulated in OS tissues, and associated with poor prognosis in OS patients. Functionally, METTL16 substantially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Besides METTL3, KIAA1429, YTHDF3, METTL16, WTAP, RBM15 and ALKBH5 are identified to regulate OS progression [ 15 , 181 , 185 , 187 , 192 , 201 ]. It is reported that KIAA1429 knockdown decreases the activity of JAK2/STAT3 signal to decreased cell proliferation, migration, and invasion of OS, which can be rescued by JAK2/STAT3 stimulator colivelin [ 188 ].…”
Section: M6a and Skeletal System Diseasementioning
confidence: 99%
“…Besides METTL3, KIAA1429, YTHDF3, METTL16, WTAP, RBM15 and ALKBH5 are identified to regulate OS progression [ 15 , 181 , 185 , 187 , 192 , 201 ]. It is reported that KIAA1429 knockdown decreases the activity of JAK2/STAT3 signal to decreased cell proliferation, migration, and invasion of OS, which can be rescued by JAK2/STAT3 stimulator colivelin [ 188 ].…”
Section: M6a and Skeletal System Diseasementioning
confidence: 99%
“…With roles in SAM homeostasis, differentiation, and DNA-damage response, METTL16 is an essential protein in normal human cells (T. Wang et al, 2015) and genetic knockout of Mettl16 in mice results in embryonic lethality (Mendel et al, 2018;Yoshinaga et al, 2022). Recent analyses suggest that METTL16 may play a role in human health and disease because (i) METTL16 is upregulated in multiple cancers including AML (L. Han et al, 2023), breast cancer (F. Ye et al, 2023;, colon cancer (S. Wang, Fan, et al, 2021), esophageal cancer (H. Zhao, Xu, et al, 2021), hepatocellular carcinoma (R. Su, Dong, et al, 2022), osteosarcoma (Cheng et al, 2023), and stomach cancer (X. K. , and (ii) METTL16 is downregulated in liver cancer (W. Wang, Sun, et al, 2020), patients with hepatocellular carcinoma (P. , cases of infertility (S. Zhao, Lu, et al, 2021), and instances involving the absence of gut microbiota (Jabs et al, 2020). Interestingly, a recent study found that METTL16 is the most crucial METTL protein for cancer survival out of 25 METTLs and that knockout of METTL16 in hepatocellular carcinoma, where METTL16 is overly abundant, led to the suppression of tumorigenesis (R. Su, Dong, et al, 2022).…”
Section: Methyltransferase-like Protein 16mentioning
confidence: 99%
“…METTL16 induced m6A modification of VPS33B and impaired its transcript stability (Cheng et al, 2023).…”
mentioning
confidence: 98%
“…The authors found that KO of PLAP‐1/Asporin inhibited osteoclast differentiation while promoted osteogenic differentiation, which at least in part through TGF‐β1/Smad signaling pathway (Liu et al, 2023). Furthermore, Cheng et al (2023) reported a novel function of methyltransferase‐like 16 (METTL16), a newly identified methyltransferase, in osteosarcoma (OS). Vacuolar protein sorting protein 33b (VPS33B) was identified as a downstream target of METTL16.…”
mentioning
confidence: 99%
See 1 more Smart Citation